Study on mechanical characterization plastics waste as coarse aggregate (PWCA) for concrete - Rozaimah Ramly
In this final year project, plastics waste can be collected from the trash bag plastics only. The plastics waste to be used replace as coarse aggregate in concrete. The characterization were analyzed in terms of physical properties aggregate such as size and shape, surface texture, colours, water absorption and slump test. The test for evaluating the mechanical properties of the concrete with plastics waste aggregate was conducted such as compression test and flexural test.